Genome-Wide Identification of Wheat WRKY Gene Family Reveals That TaWRKY75-A Is Referred to Drought and Salt Resistances - Ye, Hong; Qiao, Linyi; Guo, Haoyu; Guo, Liping; Ren, Fei; Bai, Jianfang; Wang, Yukun (Frontiers in Plant Science, 2021)
It is well known that WRKY transcription factors play essential roles in plants’ response to diverse stress responses, especially to drought and salt stress. However, the comprehensive analysis of this family in wheat is still missing. Here, we sued in silico analysis and identified 124 WRKY genes including 294 homoeologous copies from high quality reference genome of wheat (Triticum aestivum). We also found TaWRKY gene family did not undergo gene duplication rather than gene loss during evolutionary process. TaWRKY family members displayed different expression profiles under several abiotic stresses, indicating their unique functions in the mediation of particular responses. Further, TaWRKY75-A was highly induced after PEG and salt treatments. Ectopic expression of TaWRKY75-A in Arabidopsis enhanced drought and salt tolerance. Comparative transcriptome analysis demonstrated that TaWRKY75-A integrated jasmonic acid biosynthetic pathway and other potential metabolic pathways to increase drought and salt resistances in Arabidopsis. Our study provides valuable insights into WRKY family in wheat and will generate useful genetic resource for improving wheat breeding.